Efficacy of clopidogrel and ticagrelor under NT-proBNP in hospitalized ST-elevation acute coronary syndrome patients on percutaneous coronary intervention: CCC-ACS Project Analysis. (1st July 2020) - Zhao, Xin; Ai, Guannan; Qiu, Miaohan; Wang, Xiaozeng; Zhang, Lei; Yang, Xiaoxu; Liu, Yifei; Xu, Pei; Zhang, Jiyuan; Gu, Chonghuai; Zhou, Mengge; Hao, Yongchen; et al.
Abstract: Background: Risk stratification with specific biomarkers is proposed for tailored P2Y12 inhibitor therapy in patients with STEMI. Methods: This nationwide registry and quality improvement study is from November 1, 2014, to June 30, 2017. In total, 11, 512 STEMI patients received aspirin and P2Y12 receptor inhibitor (clopidogrel or ticagrelor) and underwent PCIs in hospitals. Of the patients, 2992 were prescribed ticagrelor and 8520 clopidogrel. The primary effectiveness outcome was major adverse cardiovascular and cerebrovascular events (MACCE: cardiac death, myocardial infarction, stent thrombosis, in-hospital ischemic stroke). The primary safety outcome was in-hospital major bleeding. Results: MACCE incidence was lower in the ticagrelor group than in the clopidogrel group (0.8% versus 1.2%; P =0.046), but under different NT-proBNP levels, cumulative hazards of MACCE were without statistical significance. Bleeding rates were higher in the ticagrelor group than in the clopidogrel group (all bleeding: 9.9% versus 6.9%, P <0.001; major bleeding: 4.0% versus 2.7%, P <0.001). The higher cumulative hazard of bleeding could be identified in the Kaplan–Meier curves. In the multivariate analysis, ticagrelor increased bleeding events, compared with clopidogrel, at NT-proBNP >1800 ng/L patients (all bleeding: HR 1.46; 95%CI, 1.07–2.01; major bleeding: HR 1.68, 95%CI, 1.03–2.74), but a low effect was found in those with lower NT-proBNP level. Subgroup analyses show that ticagrelor increased major bleeding in patients with left ventricular ejection fraction (LVEF) <0.50 (HR 3.29; 95% CI 1.61–6.74) (interaction p =0.03). Conclusion: We found that ticagrelor, compared with clopidogrel, increased bleeding complications in hospitalized patients with NT-proBNP>1800 ng/L, especially in patients with EF < 0.50. Highlights: This is the first registry study to assess the effect of DAPT on 15-day hospitalization outcomes in Chinese patients. This study shows that ticagrelor increased bleeding complications in hospitalized patients with NT-proBNP>1800 ng/L. NT-proBNP>1800 ng/L patients may benefit from clopidogrel vs ticagrelor with safety outcome.